2016
DOI: 10.1002/wsbm.1371
|View full text |Cite
|
Sign up to set email alerts
|

Computational models of the neural control of breathing

Abstract: The ongoing process of breathing underlies the gas exchange essential for mammalian life. Each respiratory cycle ensues from the activity of rhythmic neural circuits in the brainstem, shaped by various modulatory signals, including mechanoreceptor feedback sensitive to lung inflation and chemoreceptor feedback dependent on gas composition in blood and tissues. This paper reviews a variety of computational models designed to reproduce experimental findings related to the neural control of breathing and generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
136
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(138 citation statements)
references
References 96 publications
(337 reference statements)
1
136
1
Order By: Relevance
“…We have extended our previous firing-rate based model of the respiratory central pattern generator to account for differential respiratory responses to perturbations of glycinergic and GABAergic transmission within the BötC (Figure 5). The respiratory circuitry in this model was based on the respiratory circuitry presented in a series of previous models that examined the emergence of active expiration as well as gas-exchange and pulmonary feedback (Rubin et al, 2009, Rubin et al, 2011, Molkov et al, 2014, Molkov et al, 2016). The network connectivity in these models was informed by brainstem transection experiments presented in Smith et al (2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have extended our previous firing-rate based model of the respiratory central pattern generator to account for differential respiratory responses to perturbations of glycinergic and GABAergic transmission within the BötC (Figure 5). The respiratory circuitry in this model was based on the respiratory circuitry presented in a series of previous models that examined the emergence of active expiration as well as gas-exchange and pulmonary feedback (Rubin et al, 2009, Rubin et al, 2011, Molkov et al, 2014, Molkov et al, 2016). The network connectivity in these models was informed by brainstem transection experiments presented in Smith et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacological or optogenetic suppression of the pFRG neurons eliminates the abdominal expiratory activity evoked by hypercapnia or stimulation of peripheral chemoreceptors (Zoccal et al, 2018, de Britto and Moraes, 2017, Marina et al, 2010, Moraes et al, 2012a, Lemes et al, 2016), indicating that pFRG neurons are necessary for the emergence of active expiratory pattern. How pFRG oscillator interacts with other respiratory compartments within the brainstem, especially with the core of respiratory network, was theoretically hypothesized (Molkov et al, 2016, Molkov et al, 2014, Rubin et al, 2011, Molkov et al, 2010), but largely remains an unresolved question.…”
Section: Introductionmentioning
confidence: 99%
“…; Molkov et al . ). With the latter omission, we felt it was not appropriate to explore recruitment of abdominal outputs and forced expiration such as in hypercapnia, as has been discussed by others (Molkov et al .…”
Section: Discussionmentioning
confidence: 97%
“…In spite of the fact that the ventral medullary neurons are responsible for generating the respiratory rhythm (Richter & Smith, 2014;Smith et al, 1991), the stimulation of sensory afferents, c 2018 The Authors. Experimental Physiology c 2018 The Physiological Society including baroreceptor inputs, leads to significant changes in the breathing pattern (Dick et al, 2005;Molkov, Rubin, Rybak, & Smith, 2017). Baekey, Molkov, Paton, Rybak, and Dick (2010) reported that baroreceptor stimulation during expiration prolongs the expiratory duration.…”
Section: Introductionmentioning
confidence: 99%